Identification of novel Phytophthora infestans small RNAs involved in potato late blight reveals potential cross-kingdom regulation to facilitate oomycete infection. (19th May 2020) - Chang, Haowu; Zhang, Hao; Qin, Qing-Ming; Zhang, Tianyue; Zhang, Teng; Liu, Yuanning; Liu, Haiming; Zhong, Xiaodan; Song, Shizeng; Li, Cong; Shen, Bowen
Potato late blight, caused by the oomycete Phytophthora infestans, is one of the most devastating potato diseases. However, the pathogenesis of the oomycete pathogen remains mostly obscure. Small RNAs (sRNAs) of fungal pathogens and host plants have proven to be closely related to their interactions. Based on analysing differentially expressed sRNA data before and after infection of P. infestans, this paper obtains potential transboundary regulation fungus sRNAs and analyses their essential characteristics and functions. The result shows that sRNAs of the oomycete pathogen P. infestans likely possess the capacity of cross-kingdom regulation of potato growth and defence. The prediction model of P. infestans sRNAs related to the cross-kingdom regulation and pathogenic process provides a new analytical approach for the study of host infection by oomycete pathogens and contributes to our understanding of the interaction between oomycete pathogens and their host plants.